Teoria critica decolonial sobre um vazio epistemológico na academia brasileira - João José Veras de Souza (Nepan editor, 2015)
This article briefly introduces Decolonial theory, its position on the idea of modernity, and the epistemologies that originated from it, especially through Social Sciences and Humanities, in Latin America. This work attempts at drawing attention to an “epistemological void” in Brazilian academia, namely the absence of a proper dissemination of the so-called post-colonial studies, which would have opened the possibility to access a different knowledge model, against the quasi-total domination of social theories coming from Europe and the US. Therefore, the article brings to debate an empiric case-study of this void in Brazilian academia: the syllabus of the module “Theory of Society, Politics and Nature” – from the Interdisciplinary Postgraduate curse in Humanities of the Federal University of Santa Catarina (UFSC).